A Dip Test Strip Based on Immobilized Pararosaniline for Detection of Formalin Adulteration in Tofu - Kuswandi B.; Riskyna A.; Ahmad M. (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS